Pemberdayaan Siswa melalui Pelatihan Kreatif Ecobrick: Meningkatkan Keterampilan dan Kepedulian Lingkungan di Sekolah Dasar: Student Empowerment through Creative Training Ecobricks: Improving Skills and Environmental Awareness in Elementary Schools - Ramadani, Ahmad; Lestari, Aprilia Eka; Saputra, Bayu; Christian Radiafilsan; Adelia, Cindy; Santosa, Dewa Damar Wulan Putra; Kurniawan, Dony; Habeahan, Frederika Juliani; Perangin-Angin, Ghabrylla Br; Adeputra, Gio Tama; Paujiah, Idah Lisna; Kamuri, Iqbal Achmad; Ermelinda D.C., Juhana; Yuniati, Nisa; Sinurat, Skolastika Irawati Br; Sumiati, Sumiati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Plastic waste management has become a significant environmental challenge, particularly in urban areas. SD Negeri 2 Tumbang Talaken in Central Kalimantan faces issues with plastic waste management, with most waste being disposed of carelessly. One solution implemented is the Ecobrick method, which utilizes used plastic bottles to process plastic waste into valuable products such as furniture or building materials. This Ecobrick training program aims to raise students' awareness of the importance of waste management and teach them skills in recycling plastic waste into valuable items. The method involves educating students about the importance of waste management and hands-on practice in making Ecobricks by compacting plastic waste into used bottles. The training results showed an increase in students' understanding of waste management and creativity in producing Ecobricks, which can be used for school decorations or furniture. This program also supports character development in line with the Merdeka Curriculum, while contributing to the creation of an environmentally friendly school. The success of this program opens opportunities to involve more schools in efforts to reduce plastic waste and promote sustainable environmental management.